Deskripsi Kondisi dan Penggunaan Media Nonproyeksi Dalam Pembelajaran Matematika di Sekolah Dasar Negeri 73 Pontianak Barat - Kania Indira Putri; Bistari Bistari; Siti Halidjah (Departement of Mathematics Education, 2023)
This study aims to describe the conditions and use of non-projection media in learning mathematics of State Elementary School 73 West Pontianak. The research methode used is descriptive method. There are 2 data sources in tis study, primary data sources is educators, and secondary data sources is observation sheets, inteview guides and documentation. Data analysis uses the Miles and Huberman model. The results of the study show that the condition of non-projection media in learning is in good condition and can function, but the use of non-projection media is rarely used by teachers during the learning process